3D Printing Pharmaceuticals: Drug Development to Frontline Care. (May 2018) - Trenfield, Sarah J.; Awad, Atheer; Goyanes, Alvaro; Gaisford, Simon; Basit, Abdul W.
Abstract : 3D printing (3DP) is forecast to be a highly revolutionary technology within the pharmaceutical sector. In particular, the main benefits of 3DP lie in the production of small batches of medicines, each with tailored dosages, shapes, sizes and release characteristics. The manufacture of medicines in this way may finally lead to the concept of personalised medicines becoming a reality. In the shorter term, 3DP could be extended throughout the drug development process, ranging from preclinical development and clinical trials, through to frontline medical care. In this review, we provide a timely perspective on the motivations and potential applications of 3DP pharmaceuticals, as well as a practical viewpoint on how 3DP could be integrated across the pharmaceutical space. Highlights: 3DP enables the precise deposition of drug and excipients, potentially causing a paradigm shift in medicine design, manufacture and use. Early-phase drug development (such as preclinical studies and first-in-human trials) could be expedited by using 3DP to rapidly produce formulations with excellent dose flexibility at low cost, on demand. 3DP could support formulation development because it has the capability to produce rapid product iterations for testing, such as excipient compatibility and drug release. 3DP could accelerate the field of personalised medicine by moving treatment away from a 'one size fits all approach' towards personalisation.